Characterization of SgALMT genes reveals the function of SgALMT2 in conferring aluminum tolerance in Stylosanthes guianensis through the mediation of malate exudation - Miao, Ye; Hu, Xuan; Wang, Linjie; Schultze-kraft, Rainer; Wang, Wenqiang; Chen, Zhijian (Elsevier, 2024)
Aluminum (Al) toxicity is the major constraint on plant growth and productivity in acidic soils. An adaptive mechanism to enhance Al tolerance in plants is mediated malate exudation from roots through the involvement of ALMT (Al-activated malate transporter) channels. The underlying Al tolerance mechanisms of stylo (Stylosanthes guianensis), an important tropical legume that exhibits superior Al tolerance, remain largely unknown, and knowledge of the potential contribution of ALMT genes to Al detoxification in stylo is limited. In this study, stylo root growth was inhibited by Al toxicity, accompanied by increases in malate and citrate exudation from roots. A total of 11 ALMT genes were subsequently identified in the stylo genome and named SgALMT1 to SgALMT11. Diverse responses to metal stresses were observed for these SgALMT genes in stylo roots. Among them, the expressions of 6 out of the 11 SgALMTs were upregulated by Al toxicity. SgALMT2, a root-specific and Al-activated gene, was selected for functional characterization. Subcellular localization analysis revealed that the SgALMT2 protein is localized to the plasma membrane. The function of SgALMT2 in mediating malate release was confirmed by analysis of the malate exudation rate from transgenic composite stylo plants overexpressing SgALMT2. Furthermore, overexpression of SgALMT2 led to increased root growth in transgenic stylo plants treated with Al through decreased Al accumulation in roots. Taken together, the results of this study suggest that malate secretion mediated by SgALMT2 contributes to the ability of stylo to cope with Al toxicity.